2017
DOI: 10.1016/j.mimet.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Most probable number - loop mediated isothermal amplification (MPN-LAMP) for quantifying waterborne pathogens in < 25 min

Abstract: We are reporting a most probable number approach integrated to loop mediated isothermal technique (MPN-LAMP) focusing on Gram-negative Escherichia coli and Gram-positive Enterococcus faecalis bacterial cells without nucleic acids extraction. LAMP assays for uidA from E. coli and gelE from E. faecalis were successfully performed directly on cells up to single digit concentration using a commercial real time PCR instrument. Threshold time values of LAMP assays of bacterial cells, heat treated bacterial cells (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In our study, the optimal temperatures were 60 and 61ºC for the detection of E. faecalis and E. faecium, respectively, in the LAMP assay. However, a recent study showed no difference in gene amplification conditions between Gram-negative and Gram-positive bacteria in the LAMP assay (19). In another study, the optimum temperature was 65ºC for gene amplification in the LAMP test for the detection of E. faecalis (6).…”
Section: Discussionmentioning
confidence: 94%
“…In our study, the optimal temperatures were 60 and 61ºC for the detection of E. faecalis and E. faecium, respectively, in the LAMP assay. However, a recent study showed no difference in gene amplification conditions between Gram-negative and Gram-positive bacteria in the LAMP assay (19). In another study, the optimum temperature was 65ºC for gene amplification in the LAMP test for the detection of E. faecalis (6).…”
Section: Discussionmentioning
confidence: 94%
“…Researchers also attempted to completely avoid nucleic acid isolation and instead apply the sample directly into the isothermal amplification mix. This has been demonstrated for plants using the example of papaya [ 15 ] and for the fecal indicator bacteria E. coli and E. faecalis [ 16 ]. The authors concluded that the elevated temperature of 63 °C could lead to increased cell permeability, allowing direct amplification of the target DNA.…”
Section: Case Study: Towards Implementing a Field-applicable Workflowmentioning
confidence: 99%
“…Ahmad and others () used the most probable number approach with LAMP (MPN–LAMP) for detection of Gram‐negative E. coli and Gram‐positive Enterococcus faecalis without NA extraction. This method can be applied directly to the bacterial cells, which reduces the chances of NA loss during upstream sample processing, thus it is more effective in detecting target NA.…”
Section: Loop‐mediated Isothermal Amplificationmentioning
confidence: 99%